Link between the albumin-corrected anion gap and 28 day all‑cause mortality among patients with sepsis complicated with chronic heart failure: A retrospective analysis using the eICU Collaborative Research Database - Chen Zhang; Ali Ma; Juan Ma; Peng Wu; Huiyan Ma; Xueping Ma; Ning Yan (PLoS ONE, 2025)
Background These two conditions, namely metabolic acidosis and hypoproteinemia, are prevalently observed in patients within intensive care units (ICU), particularly those with sepsis complicated with chronic heart failure. Nevertheless, the impact of the Albumin-Corrected Anion Gap (ACAG), an indicator reflecting the above conditions, on such patient mortality requires further investigation. This retrospective cohort study analyzed the significance of ACAG levels in forecasting 28-day all-cause mortality among these patients admitted to ICU. Methods This was observational cohort study on eICU Collaborative Research Database (eICU-CRD) that included in participants with sepsis complicated with chronic heart failure. In the study, we applied several methods such as multivariate Cox regression models and smooth curve fitting plots combined with Kaplan-Meier analysis to investigate how ACAG is correlated with 28 day all‑cause mortality. To explore the results’ stability, subgroup analysis was performed and a forest plot was plotted. Results The final analysis included 713 eligible participants after rigorous screening procedures. The mean level of ACAG was (16.68 ± 5.20) mmol/l. The 28-day mortality rate was 13.60% (97/713) in our study. The multivariate Cox regression analysis revealed a significant association between ACAG (as a continuous variable) and 28-day all-cause mortality, unadjusted model (HR 1.07, 95% CI 1.04–1.11, p < 0.0001), adjusted model 1 (HR 1.08, 95% CI 1.04–1,12, p < 0.0001), adjusted model II (HR, 1.08 (1.03,1.13), p < 0.001). After adjusting for all confounding factors (listed in the Model II), the smoothing curves showed a linear relationship. Mortality in such patients gradually increased with the increase of ACAG according to Kaplan-Meier analysis. Subgroup analysis illustrates the stability of the link between ACAG and 28-day mortality in participants with sepsis complicated with chronic heart failure across various subgroups. Conclusions After adjusting for confounding factors, elevated ACAG is positively linked with increased 28-day mortality in patients with sepsis complicated with chronic heart failure.